Incidencia de los titulares en el consumo de los contenidos informativos del diario Extra en la parroquia de Guaytacama. - Barrera Ruiz, María Belén (2018)
The newspaper is considered, by readers, a traditional medium for its transcendence and historical heritage. In the research project an analysis is made to determine how the headlines incidence in the Extra newspaper consumption of its informative contents in the parish of Guaytacama. Since, a headline is considered the hook for the reader to consume news. A mixed design methodology was used in this project through the qualitative and quantitative approach. Consequently, a survey was applied to 15 taxi drivers from "Las Totoras" cooperativa of the Guaytacama, parish considering that this group consumes the Extra newspaper the most. In addition, in-depth interviews were conducted with six people from an age range of 30 to 50, because each person has a different criterion. Finally, an analysis sheet was made, with the purpose of studying the main headlines of the newspaper. The results, through this study, determine that the headlines, especially topics such as Cronica Roja, affect the purchase of it. According to the survey, the overdone headlines are the ones that affect readers' interest in the rest of the news, the more striking the headlines, the more interest it will cause in the audience for its consumption. The population interviewed said that they want to consume this newspaper because it contains overdone information, and both headlines and images can be a bad reference for the education of underage. However, society accepts it and consumes it even though it is considered a sensationalist media. Through the analysis card it is evident that the extra is characterized by the sensationalism in its contents, because it presents titles with overdone messages, it uses an everyday language oriented to highlight the news. In addition the color, size and shape of the headlines are designed to capture the reader's attention. In conclusion, the headlines disseminated by the Extra newspaper, influence the acquisition of their copies, in such a way, the audience is attracted by the use of the jargon, and the use of a common vocabulary.